2019
DOI: 10.21303/2461-4262.2019.00836
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study the Performance of Ram Water Pump

Abstract: Ram water pump is one types of renewable energy that work without any source when used to provide energy from water power for changing the potential energy to kinetic energy to use for agriculture fields. The device must find near the rivers to useful from water to work and the waste water return to the river again. The performance of the ram pump is studied experimentally. The device is simple contain from fittings, tank, pipes, pressure vessel and valves. Three inlet diameter (1/2, 3/4 and 1 in) at inlet pip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
1
5
0
2
Order By: Relevance
“…In addition, the higher delivery head (Hd) generated a smaller pumping discharge. It was agreeing to [14] results which stated that the delivery head and the pumping flow rate have inversely relationship.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, the higher delivery head (Hd) generated a smaller pumping discharge. It was agreeing to [14] results which stated that the delivery head and the pumping flow rate have inversely relationship.…”
Section: Resultssupporting
confidence: 88%
“…The pressure of water proportional to the length of the drive pipe, meanwhile it increased the pressure loss occurring [13]. Moreover, diameter of the drive pipe affected the quantity of water flowing through the impulse valves and efficiency of the pump [14]. A back-enlargement on the hydraulic ram model was proposed to decrease head loss and drag coefficient [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, Oliveira (2011) reported that it is necessary to seek more viable alternatives to avoid waste, considering that the water use is becoming increasingly restricted. To solve this problem, Dhaiban (2019) suggested techniques for building a system to collect and direct wastewater to the tank. With regard to the number of valve beats, a relationship inversely proportional to the volume of the air chamber was found.…”
Section: Resultsmentioning
confidence: 99%
“…The hydram pump takes in water at a relatively low pressure with high flow-rate and outputs water at a higher hydraulic head with lower flow-rate. [8] Furthermore, the efficiency calculation table and graphic chart is provided below If we look at the graphic chart, we can safely conclude that the efficiency of a hydram pump is diminishing the higher the output pipe. The efficiency is also directly proportional to the input discharge because the efficiency rate is rising if we increase the input value.…”
Section: Resultsmentioning
confidence: 99%